Treatment of Residential Complexes' Wastewater using Environmentally Friendly Technology. (2017) - Alattabi, Ali Waheid; Harris, Clare; Alkhaddar, Rafid; Alzeyadi, Ali; Hashim, Khalid
Abstract: Residential complexes discharge huge quantities of wastewater, which has a negative impact on nearby water bodies. Moreover, the treatment of this type of wastewater requires a large area, which could be a challenge as construction sites are normally limited in size. Different technologies have been used for the treatment of residential complexes' wastewater (RCWW). Compared to the conventional wastewater treatments methods, sequencing batch reactors (SBRs) are lower cost and have smaller area requirements and sludge bulking rarely occurs. A considerable number of researchers have been optimising SBR operating conditions to gain a better removal efficiency of undesired wastewater pollutants. However, many researchers have reported bad, slow or incomplete particle settling. This study examines the impact of organic loading rate (OLR) on the effluent quality and sludge settling performance in a sequencing batch reactor. Four SBR reactors were used in this study; the working volume of each one is 5l. The reactors were operated under different glucose concentrations (750, 1000, 1250 and 1500 mg/l), constant aeration, 1.0 l/min, ±20 C° temperature and 6 h cycle time. Each cycle of the SBR operation included Fill (30 minutes), React (240 minutes), Settle (30 minutes), Draw (30 minutes) and Idle (30 minutes). Influent and effluent samples were analysed for COD, NH3-N, NO3-N and NO2-N. In addition, the sludge volume index (SVI) and a morphological study were used to study the sludge characteristics. The SVI and morphological study results showed a direct relationship between the glucose concentration and sludge settling behaviour. The results obtained from this study, which operated for 120 days, showed that the sequencing batch reactor could biodegrade up to 93.2%, 95.2%, 94.9% and 96.5% for COD, NH3-N, NO3-N and NO2-N respectively with glucose concentration between 750 and 1250 mg/l, and a steady sludge settling performance occurred during that range.